The modernization of the Labor Law (Revista da Faculdade de Direito, Universidade de São Paulo, 1999)
The economic changes at the end of the twentieth century lead to the need for the modernization of Labor Law. This kind of Law must be adapted to a new reality in which the technological innovations and the market competitiveness demand changes in the relations between employees and enterprises. Therefore, the revision of the Brazilian system of union organization, the increase of collective contracts and the creation of a new role for the State are indispensable.